Association between a low dose of proton pump inhibitors and kidney function decline in elderly hypertensive patients: a retrospective observational study. Issue 4 (April 2021) - Wakabayashi, Tomohito; Hosohata, Keiko; Oyama, Saki; Inada, Ayaka; Niinomi, Iku; Kambara, Hiroko; Iida, Tatsuya; Hasebe, Keiko; Matsuoka, Hiroyuki; Uchida, Mayako; Kumagai, Etsuko
Objectives: Proton pump inhibitors (PPIs) are widely used for acid suppression therapy. Recently, PPI use was reported to be associated with chronic kidney disease (CKD); however, whether a low dose of PPIs is associated with CKD remains unknown. Methods: This retrospective observational study included hypertensive patients who visited Kenwakai Hospital between 2017 and 2019. Renal parameters, such as the estimated glomerular filtration rate (eGFR) and serum creatinine (Scr), were extracted from medical records and compared between three years before treatment and the baseline. PPI use was assessed as cumulative exposure for three years. Results: The study population included 152 patients (57.9% men; mean age, 74.5 years). Of those, 35.5% were PPI users (low dose, 17.1%; high dose, 18.4%). A significant decrease in eGFR and an increase in Scr were observed between three years before treatment and the baseline in the high-dose PPI group but not the non-use or low-dose PPI groups. Conclusions: Our results suggest that a low dose of PPIs may be safe in clinical settings, but further prospective studies are needed to clarify our findings.